ESL writing conference: expectations and revisions in the subsequent draft - Ritthirat, Karanrat, author; Becker, Tony, advisor; Nekrasova-Beker, Tatiana, committee member; Kaiser, Leann, committee member (Colorado State University. Libraries, 2017)
Although the area of L2 feedback has been widely investigated (eg, Ferris, 2004; Ferris & Roberts, 2001; Goldstein & Conrad, 1990), there has been little research examining students' expectations of writing conferences and their uptake in subsequent drafts. These issues need to be further studied since they could promote better writing conferences and create a better understanding between instructors and students. The purpose of the present study is threefold: 1) to gauge ESL students' expectations towards writing conferences, 2) to determine types of feedback students received during one-on-one writing conferences, and 3) to examine students' uptake in subsequent drafts. Employing a mixed-methods design, data was collected using surveys and interviews to examine students' (n=29) expectations before and after each writing conference that took place between instructors and students. The results showed that students expected their instructor to focus on content and organization the most, followed by the expectation that the conference would make them feel that their instructor cared about them as an individual. In addition, most students successfully took up the feedback they received into their subsequent draft. The findings suggest that prior to a conference, students should be informed of what they are expected to do during a one-on-one discussion since students from different cultural backgrounds can have different perspectives towards personal interaction with their teacher.